Morphology, tensile strength and oil resistance of gum rubber sheets prepared from lignin modified natural rubber - Asrul, M. (EDP Sciences, 2014)
The paper describes the preparation of lignin filled natural rubber latex composite and its subsequent use to obtain lignin modified rubber. Two types of lignin i.e.: rubber wood and commercial alkali lignin were used as rubber filler. Gum rubber sheets were prepared from the lignin modified rubber and their properties were compared to Standard Malaysian Rubber (SMR 20) and a type of rubber obtained from the coagulation of high ammonia latex. Rubber morphology was investigated using Scanning Electron Microscope on the cross-sectional area of cryo-fractured samples. Oil resistance of the rubber sheets was determined by measuring the mass change before and after ASTM IRM 903 oil immersion, while the tensile strengths were determined according to ASTM D412 standard. Low values of tensile strength obtained for the commercial alkali lignin modified rubber sheet relative to the rest of the rubber samples was attributed to poor lignin dispersion. This occurrence was substantiated by the SEM analysis of cryo-fractured samples where crazes and inhomogeneity was observed. Nonetheless, both lignin modified rubbers exhibited higher level of oil resistance compared to SMR 20. This is due to the nature of lignin as a hydrophilic component and its presence in the rubber matrix complicates the oil diffusion process into rubber. Â© 2014 Owned by the authors, published by EDP Sciences.